A new Werauhia (Tillandsioideae, Bromeliaceae) from Mexico with observations about its reproductive biology - Aguilar-Rodríguez, Pedro A.; Díaz Jiménez, Pedro; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Hentrich, Heiko; Dötterl, Stefan; Yovel, Yossi; Macswiney-G., M. Cristina (Phytotaxa, 2020)
Werauhia maculata a new species from Tabasco, Mexico is described and illustrated. The new taxon possesses a large tank-rosette, with conspicuous and irregularly disposed dark purple marks on the basal portion of the leaves abaxial surface, a simple inflorescence, with secund and numerous whitish-flowers densely arranged on the rachis. The new taxon is compared with W. pectinata and W. noctiflorens, species with similar characteristics. In addition, some data about its reproductive biology are presented.